THE LEGAL BASIS OF THE STATE'S DEFENSE CAPABILITY (Scientific journal of the Fergana State University, 2025)
The article examines the issues of the state's defense capability as an important factor in ensuring national security and compliance with legal norms, as well as international and national legal norms, which are the fundamental elements in this area.